Culture Shock: A New Life of An Indonesian Student Adapting to The U.S. Life - Teddy Fiktorius (Sosial Budaya, 2019)
In recent years, the growing trend of globalisation has significantly made culture shock start to be experienced by more people around the world. This paper takes the theoretical base of culture shock into account and pays close attention to how an Indonesian student adapted to some new cultural patterns of the U.S. college life. First of all, the four stages of culture shock are elaborated. Next, it describes a sequence of experiences and feelings of the informant when dealing with some adaptation to the U.S. college life and culture. Finally, this paper emphasises some noticeable points of the culture shock intensity.